Developing surface ionisation charge-transfer dynamics of hydrogen Rydberg atoms into an energy-resolved probe of surfaces - Kohlhoff, M (2016)
As a Rydberg atom approaches a surface, it will eventually undergo ionisation by charge transfer into the surface at a distance of about 100nm (for principal quantum numbers n > 20). The dynamics of this process are sensitive to the electronic and geometric structure of the surface and can display signature characteristics. As such, Rydberg atoms can be used to probe image-charge effects or to measure small superficial electric stray or patch fields. The charge-transfer process can be in resonance between the Rydberg energies and the energetically discrete surface states (image states) in a bandgap. Surface ionisation of Rydberg atoms is investigated for graphene, which is a zero-bandgap semiconductor and can behave either as a metal or a semiconductor. The charge-transfer dynamics observed here exhibit the characteristics of a metal with enlarged ion detection efficiency compared to a copper sample -- in accordance with other properties of graphene, such as conductivity, that are enlarged compared with a regular metal. For hydrogen Rydberg atoms, surface ionisation is detected for distances up to 10 µm, with a double series of high-lying image states extending far from the graphene film possibly creating a quasi-continuum at large atom-surface separations with a density of states beyond the resolution of the Rydberg states from n=20 to 40. The resonance behaviour for graphene is explored with a range of Rydberg H-atom collisional velocities whose effect on the charge transfer process introduces an additional handle on the probing of electronically discrete features of a surface. A wave-packet propagation study of a hydrogen atom incident at a free-metal surface up to n=20 displays shifts in ionisation towards greater distances and over a narrower range when acceleration of the ion core is not included. The thereby significantly reduced effect of the collisional velocity of Rydberg surface ionisation is also observed in an experimental study with a limited velocity range available from supersonic expansion directed at a gold sample. This either suggests that the range of Rydberg projectile velocities is to narrow to have observable effects or that a pronounced velocity dependency is merely detected for distinct electronic resonances. With the aim to further elucidate the velocity dependence and to prospectively remove ambiguities that arise from the nature of the experiment, a chip-based decelerator is constructed and integrated into the experimental apparatus for the first time. Within the constraints of the design and the existing apparatus, the chip device is not able to produce sufficient densities of decelerated particles to be employed in surface-ionisation experiments. Extensive modelling of the deceleration process indicates that modifications to the existing design and the experimental apparatus could achieve a tunable-velocity source of hydrogen Rydberg atoms with greatly enhanced densities for future investigations.